Low sense of coherence during postoperative recovery is associated with a poorer lumbar spinal stenosis – surgical outcome: A 5-year follow-up study. (March 2017) - Pakarinen, Maarit; Sinikallio, Sanna; Koivumaa-Honkanen, Heli; Aalto, Timo; Airaksinen, Olavi; Lehto, Soili M; Viinamäki, Heimo
This study investigated the association between the 3-month postoperative sense of coherence and the 5-year postoperative outcome of decompressive surgery for lumbar spinal stenosis. The participants with a lower sense of coherence at the 3-month follow-up had a poorer functional ability and lower satisfaction with surgery, higher pain ratings, lower life satisfaction and more depressive symptoms 5 years postoperatively. A low 3-month sense of coherence associated with greater pain and a poorer functional ability 5 years postoperatively. Evaluating sense of coherence and depressive symptoms in patients who have had lumbar spinal stenosis surgery may help in identifying those in need of enhanced support for postoperative recovery.